All-step mechanochemical approach for the rapid and solventless synthesis of Boscalid - Nagao, Asahi; Kubota, Koji; Ito, Hajime (Synthesis)
Boscalid, the active ingredient in various fungicides used in large quantities worldwide, is traditionally synthesized using solutionbased methods that require substantial quantities of reaction solvents and prolonged reaction times, highlighting opportunities for improvement in waste reduction, time efficiency, and energy consumption. Herein, we report a solventless and rapid synthesis of Boscalid via an all-step mechanochemical reaction. This synthetic route comprises three steps: Suzuki-Miyaura cross-coupling, zinc-mediated Béchamp reduction, and amidation with 2-chloronicotinyl chloride. Each mechanochemical reaction proceeded rapidly, and the total reaction time was significantly shorter than that of previous methods. Notably, all synthetic operations can be carried out without an inert gas atmosphere or a large amount of solvent, both of which are required under conventional solution-based conditions. Furthermore, gramscale synthesis was successfully achieved without any yield loss at each step, highlighting the potential scalability of this protocol.